The Role of Small Extracellular Vesicles and MicroRNAs in the Diagnosis and Treatment of Allergic Rhinitis and Nasal Polyps - Yiting Liu; Jichao Sha; Cuida Meng; Dongdong Zhu (Mediators of Inflammation)
Allergic rhinitis and nasal polyps are common otorhinolaryngological diseases. Small extracellular vesicles and microRNAs have recently become major research topics of interest due to their key regulatory roles in cancer, inflammation, and various diseases. Although very detailed and in-depth studies on the pathogenesis and pathophysiology of allergic rhinitis and nasal polyps have been conducted, few studies have assessed the regulatory effects of exosomes and microRNAs on allergic rhinitis and nasal polyps. This paper reviews the studies on small extracellular vesicles and microRNAs in allergic rhinitis and nasal polyps conducted in recent years and focuses on the regulation of small extracellular vesicles and microRNAs in allergic rhinitis and nasal polyps with the aim of providing insights for the future diagnosis and treatment of allergic rhinitis and nasal polyps.